Construção e validação de instrumento de prevenção de quedas em hospitais pediátricos - Gurgel, Sabrina de Souza (2018)
Among the topics that cover a safe environment in health services, the possibility of occurrence of adverse events or events in hospital pediatric care, such as the fall, should be explored. The general objective was to construct and validate a pediatric hospital fall prevention instrument. Methodological study developed in three stages, namely: Step 1 - construction of the measurement instrument, produced in light of the Protocol of Prevention of Falls of the Ministry of Health; Step 2 - evaluation of the psychometric properties, in which content validity was evaluated by seven specialists through the intraclass correlation coefficient (ICC) and construct validity from the factorial analysis and contrasted groups, performed with 203 health professionals in two pediatric hospitals in the city of Fortaleza- Ceará-Brazil, as well as reliability assessment, using Cronbach's alpha, also performed with the same 203 professionals; and Step 3 - identification of actions performed by health professionals to prevent falls in the hospital environment. Study approved by the Research Ethics Committee under opinion nº 2,439,019 and nº 2,510,863. In Step 1 we obtained the first version of the instrument, entitled Instrument of prevention of falls in pediatrics (IPQP) composed of 18 items. In Step 2, in the content validation, a general ICC of 0.935, 0.810 for simplicity, 0.798 for clarity and 0.841 for relevance was obtained, obtaining the 2nd version of the instrument consisting of 15 items. In the validation of the construct, a Kaiser-Meyer- Olkin (KMO) measurement with a coefficient of 0.866 and a significant Bartlett sphericity test (p <0.001) was performed, attesting adequacy to the factorial analysis, revealing the presence of four domains, with 15 items. In the test of contrasted groups, there was a statistically significant positive association between fall prevention and participation in improvement courses, as well as the professional technical category of nursing in relation to the other categories (physician, physiotherapist and nurses). In reliability, Cronbach's alpha (0.883) indicated a high internal consistency. In Step 3, the performance of the professionals was analyzed by the positivity index (PI), in which none of the 15 actions were performed in a desirable or adequate way. Only one action was performed safely; three border actions and eleven actions in a non-existent manner. It is concluded that the IPQP is valid and reliable for evaluating the performance of health professionals to prevent falls in the hospital environment.